Health Issues of Nigerian Muslim Pilgrims in The Immediate Post-Covid-19 Era Hajj Year 2022– Part II (Non-Communicable Diseases) - Saheed, Raji; Isiaka, Ismaila; Mande, Amina Saleh; Ahmad, Adam (Jurnal Medis Islam Internasional, 2023)
Background: Hajj is an important rite in the life of devout Muslims, requiring the devolvement of physical and material resources in its execution. Limitations posed by COVID-19 on the performance of Hajj make the year 2022 hajj to be an atypical one compared to other years' international hajj. Nigerian pilgrims are peculiar as a low-and middle-income country (LAMIC) with the highest number of Muslim pilgrims from Africa. The objective of this article is to review the health implications of Hajj and peculiarities of the post- COVID 19 era, regarding non-communicable diseases in Nigerian pilgrims based on literature, the interaction of authors with pilgrims, and the experiences of an author as a pilgrim. Results: Commonly encountered non-communicable respiratory, cardiovascular, nutritional, gastrointestinal, endocrine, reproductive, neurological, and musculoskeletal health issues in Nigerian pilgrims were explored. Preventive health strategies by individual pilgrims, the national medical team of National Hajj Commission of Nigeria (NAHCON), the Ministry of Health (MOH) of the Kingdom of Saudi Arabia (KSA) and other stakeholders involved directly or indirectly in conducting Hajj rites were appraised. This includes but not limited to illness screening, chronic illness management, life style modification, medication adherence, and accident prevention. Conclusions: It was concluded that the efforts of the Kingdom of Saudi Arabia, as well as Nigeria authorities on Hajj health services, are commendable, though there are still a lot of areas that need to be improved upon.  Significant importance should be given to pre-hajj and post-hajj screening of pilgrims for communicable health issues in pilgrims to enable optimal execution of hajj task and maintenance of pilgrims’ health beyond hajj period.